Insights into the pore structure and oil mobility in fine-grained sedimentary rocks: The Lucaogou Formation in Jimusar Sag, Junggar Basin, China. (March 2022) - Pang, Xiaojiao; Wang, Guiwen; Kuang, Lichun; Li, Hongbin; Zhao, Yidi; Li, Dong; Zhao, Xin; Wu, Songtao; Feng, Zhou; Lai, Jin
Abstract: Unconventional shale/tight oil resources in fine-grained sedimentary rocks play essential roles in global energy structure. Fine-grained sedimentary rocks are characterized by complex pore assemblage and connectivity. Insights into the links between pore structure and movable oil are important for exploration and production of tight/shale oil or gas in fine-grained sedimentary rocks. A series of analyses including thin sections, mercury injection capillary pressure (MICP), and nuclear magnetic resonance (NMR) were carried out to unravel the linkage between pore structure and oil movability. Various centrifugation speeds were used in the NMR tests to remove the movable oil to obtain the movable oil saturation corresponding to various centrifugation speed. Fractal dimension is calculated from NMR T2 spectrum. Then four types of pore structures were divided according to the parameters derived from the MICP and NMR results, and the characteristics of various pore structure are summarized. From type Ⅰ to type Ⅳ, the threshold pressure, irreducible water saturation (Swi ), and the fractal dimension increased while the SHgmax, r apex, T2gm, porosity, permeability, and movable oil saturation decreased. Then the key factors controlling the movable oil saturation were investigated, including permeability, porosity, T2gm, r apex, and mineral composition of the rocks. The movable oil saturation is dominated by porosity, T2gm, fractal dimension, and r apex . Then a quantitative evaluation model of the movable oil saturation was established. In addition, the NMR logs and the derived parameters were utilized to evaluate the reservoir quality and pore structures in a single well. At last the T2 value of 25 ms (the ratio of the T2 components >25 ms to the total T2 components) was used to calculate the movable oil saturation in the upper member of the Lucaogou Formation, and the T2 value of 28 ms was used for the lower member of the Lucaogou Formation in the Jimusar Sag. The results are testified by the high-speed (10000 r /min) centrifugation NMR measurements. The results above help improve understanding of tight/shale oil enrichment and provide a new model for calculating the movable oil saturation in fine-grained sedimentary rocks. Highlights: The reservoir quality decreases from type Ⅰ to type Ⅳ pore structure. The main controlling factors of movable oil saturation are porosity, fractal dimension, r apex and T2gm . The NMR logs can be used to calculate the movable oil saturation. The T2 value calculating the movable oil saturation is different in the upper and lower sweet spot.